Protein intake and injury outcomes among fallers in the Women’s Health Initiative’s Objective Physical Activity and Cardiovascular Health in Older Women Study - Shelby G. Ziller; Leslie K. Dennis; Jeannette M. Beasley; Andrea Z. LaCroix; Jean Wactawski-Wende; Linda Snetselaar; Jane A. Cauley; Bernhard Haring; Abdul Tawab Saljuqi; Jennifer W. Bea (PLoS ONE, 2026)
Background Falls among older adults are associated with increased morbidity, mortality, and healthcare costs; therefore, it is critical to assess modifiable risk factors. This study aimed to determine if low protein intake among older women was associated with injuries among fallers. Methods The Women’s Health Initiative ancillary studies, Live Long Study (LLS), Food Intake (FI), and Objective Physical Activity and Cardiovascular Health in Older Women study (OPACH) were combined for analyses (n = 6,580; n = 1,285 fallers). Protein intake was assessed by food frequency questionnaires at LLS/FI/OPACH baseline. Participants completed fall calendars for 13 months and self-reported injuries in interviews. Logistic regression determined odds ratios (OR) and 95% confidence intervals (CI) for risk of injurious falls and falls with fracture. Diabetes medication use had a significant interaction between protein density and fall with any injury; thus, models were stratified. Results Of the participants who fell, 841 (65.4%) fell without injury, 444 (34.6%) fell with injury, and 70 (7.7%) fell with fracture. Lower protein density (<15% calories from protein) increased risk of fracture from falling (OR: 1.73; 95% CI: 1.02–2.92) compared to those with higher protein density (≥15% calories from protein). Among participants with diabetes medication use and lower protein density, the OR for any injury from falling was 5.54 (95% CI: 1.79–17.19) compared to those with higher protein density though based on a small subgroup. Conclusion Lower protein density increased risk of injurious falls. Dietary and medication screening may facilitate selection and tailoring for behavioral falls prevention to reduce injurious falls and fractures.